KEAKTIFAN ORGANISASI REMAJA MASJID DI KAMPUNG LALADON DESA PAGELARAN KECAMATAN CIOMAS KABUPATEN BOGOR - Siti Muzdalipah; Pratiwi, Tia Putri; Zahro Malihah (Jurnal Cendekia Ihya, 2025)
The presence of mosque youth in the community aims to encourage young people to engage in positive activities. However, the socialization of teenagers today is becoming increasingly worrying due to globalization. This research is based on observational results showing a decline in mosque youth organization activities, resulting in a decrease in positive activities in the Kampung Laladon environment. This study aims to: (1) Analyze the description of mosque youth organization activity (2) Identify factors influencing organizational activity (3) Examine efforts to encourage participation and activity among mosque youth members in Kampung Laladon. The research method used is field research with a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation, and the validity of the data was tested using triangulation methods of time, technique, and source. The research results show that the activity of the Jami Nurul Huda mosque youth organization in Kampung Laladon is influenced by several factors, namely: (1) Low level of responsibility of the chairman in implementing religious studies and PHBI activity events (2) Lack of understanding among members about their tasks and functions as part of the mosque youth organization. Efforts to encourage participation and activity include holding discussions and consultations between the chairman, administrators, and mosque youth members, as well as building openness and good cooperation among members.